Hubungan Antara Self Control dan Internet Addictions S Disorders pada Mahasiswa Prodi Teknologi Pendidikan Angkatan 2020 di Universitas Negeri Padang - Nasir, Dul Aris; Darmansyah, Darmansyah; Yusri, Meldi Ade Kurnia; Rahmayanti, Elsa; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the description of the results of the analysis of the relationship between self-control and Internet addictions disorders in TP FIP UNP students class of 2020. The method used was a correlational quantitative study with a sample of 95 people from a total population of 123 people. The data collection technique uses a questionnaire. Data analysis using t-test. The results of the study for Self-control the highest percentage of respondents were in the Agree (S) answer as much as 48.50% and the Internet Addictions dissoder result was the highest in the Agree (S) answer as much as 39.50%. So with this study, it can be seen that 74.37% are related to self-control in students of the Educational Technology Study Program Class of 2020. This is because students are able to control themselves so that they are not addicted to the Internet, 65.31%. In addition, based on the indicator on self-control, the Behavior Control indicator with the highest percentage is 35.33% and on the Internet Addictions Disorders indicator, the highest indicator is excessive use at 34.71%. Based on the results of the t-test, it can be concluded that there is a significant relationship between self-control and internet addictions disorders in students of the Educational Technology Study Program, Padang State University